ANTIOXIDANT POTENTIAL OF EXTRACT OF BLACK RICE, BAJAKAH WOOD ROOT AND KEBIUL SEED - Yesti, Yulia; Kintoko, Kintoko; Nugraha, Ari Satia; Putra, Billy Harnaldo; Gusriyani, Sri; Saputra, Harry Ade; Alfarisyi, Muhammad Iqbal (JURNAL KATALISATOR, 2025)
Exposure to free radicals and oxidative stress are major factors in various degenerative diseases, such as cardiovascular disease, diabetes, cancer, and neurodegenerative diseases. Therefore, the use of natural antioxidant sources is important to reduce the negative effects of free radicals. This study compares the natural antioxidant potential of black rice, bajakah root, and kebiul seeds, whereas previous studies have only identified the antioxidant potential of a single natural ingredient. This study aims to measure the antioxidant potential, such as total polyphenols, total flavonoids, and antioxidant activity, of these three natural materials using distilled water, 70% ethanol, and 96% ethanol as solvents. The experimental research method involved testing antioxidant activity and measuring total phenolics and flavonoids. The results showed that the 70% ethanol extract of black rice had the highest total polyphenol content at 6.83±0.28 mgGAE/g (0.007±0.00%), the 70% ethanol extract of bajakah wood root had the highest flavonoid content at 8.77±0.02 mgQE/g (0.009±0.00%), and the distilled water extract of kebiul seeds showed the strongest antioxidant activity based on an IC50 value of 5.96 ± 0.01 ppm. This study concluded that black rice has potential as a primary source of phenolics and anthocyanins, while bajakah wood root and kebiul seeds are sources of flavonoids with strong antioxidant activity.